Differences between roots and leaves of Semiliquidambar cathayensis by transcriptiomic analysis - ZHOU Yun; WEI Yudan; HUANG Ritao (Xibei zhiwu xuebao, 2024)
Abstract [Objective] Both the roots and leaves of Semiliquidambar cathayensis have the effect of dispelling wind and removing obstruction in the meridians, but they are different in active components such as flavonoids. Transcriptomic sequencing was performed to obtain the transcriptome information and differentially expressed genes between roots and leaves of S. cathayensis. It is important to explore the expression of the key genes involved in the active component synthesis of S. cathayensis. [Methods] We carried out transcriptomic sequencing by Illumina high-throughput sequencing technology. Additionally, differences in gene expression for the synthetic pathways of the key secondary metabolites, such as terpenes and flavonoids, were identified and analyzed by bioinformatics analysis. [Results] 59 378 differentially expressed genes (DEGs) were classified into three major classes in GO classification, involving mainly in biological process functions (50.59%). 185 DEGs were annotated in 24 categories of the KOG classification. 81 differentially expressed genes were involved in phenylpropane biosynthesis, 30 differentially expressed genes in flavonoid biosynthesis, and 86 differentially expressed genes in terpenoid biosynthesis. [Conclusion] The key enzymes involved in flavonoid synthesis, such as CHS, were up-regulated, resulting in more flavonoids in roots than leaves. The key enzymes such as CMS and HMGS may affect the accumulation patterns of terpenoids in different tissues of S. cathayensis. The transcriptomic data of roots and leaves of S. cathayensis were obtained, which laid a foundation for the study of functional identification as well as understanding the secondary metabolic pathway and regulatory mechanism of S. cathayensis.